The price-price Phillips curve in small open economies and monetary unions: Theory and empirics - Andrea Vaona (Kiel Institute for the World Economy (IfW), 2014)
This paper extends the efficiency wages/partially adaptive expectations Phillips curve, otherwise known as the price-price Phillips curve, from a closed economy context to an open economy one with both commodity trade and capital mobility. We also consider the case of a monetary union (a country) with two member states (regions). The theoretical results are a priori ambiguous. However, in the first place, on resorting to plausible numerical simulations, economic openness increases the reactiveness of inflation to the unemployment rate. In regard to a monetary union, the national unemployment multiplier in the aggregate Phillips curve decreases with the weight of the member state in aggregate employment and increases with that in output. Secondly, we show in two empirical applications that our calibration can provide informative priors for models to be estimated thanks to the Kalman filter.
Keywords: E3; E20; E40; E50; F15; F41; C22; C26; 330; efficiency wages; unemployment; Phillips curve; inflation; adaptive expectations; Kalman filter